2010
DOI: 10.1007/s00064-010-9017-6
|View full text |Cite
|
Sign up to set email alerts
|

Der gestielte Leistenlappen zur Defektdeckung an der Hand

Abstract: In a 3-year period, defect closure with a pedicled groin flap was performed in 14 patients. Indications for this procedure were the following: thumb reconstruction for lengthening and defect closure after amputation and burn injury, soft-tissue reconstruction of the dorsum of the hand after decollement and infection, soft-tissue reconstruction of the distal part of the lower arm, wrist and palm after complex and combined trauma, and plastic reconstructive preservation of multiple fingers with subsequent phalan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Another option of the reconstructive ladder is a distant flap like the groin flap. 7 Although large defect areas can be covered, this more or less historic approach comes along with an immobilization of several greater joints and a high level of discomfort for the patient. A technically more challenging and time-consuming approach is the use of microsurgical venous flow through flaps.…”
Section: Discussionmentioning
confidence: 99%
“…Another option of the reconstructive ladder is a distant flap like the groin flap. 7 Although large defect areas can be covered, this more or less historic approach comes along with an immobilization of several greater joints and a high level of discomfort for the patient. A technically more challenging and time-consuming approach is the use of microsurgical venous flow through flaps.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, George et al [67] showed the early division of various pedicled flaps using progressive compression of the skin bridge in 1996. However, a majority of groin flap case series use a minimum of a 3-week delay prior to pedicle division [68][69][70], as initially described by McGregor [14]. Regarding lower limb reconstructions, the conventional autonomization delay is considered to be slightly longer.…”
Section: Partmentioning
confidence: 99%